2017
DOI: 10.12691/ijcd-5-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and the Gluten-free Diet: Registered Dietitian Nutritionists’ Self-reported Knowledge Varies

Abstract: Background: Adherence to the gluten-free diet is the only treatment for celiac disease (CD) and some patients report lack of expertise among registered dietitian nutritionists (RDNs). Objective: To measure RDN self-reported celiac disease (CD) knowledge and preferences for resources for self-education and patient education. Methods: A cross-sectional research design was used to recruit RDNs from participating state affiliates Alaska, Colorado, Connecticut, Delaware, Montana, Nebraska, and North Dakota in 2013.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…In Australia, dietitians had a 73% score in the knowledge about appropriate food for CeD and 69% in the knowledge related to screening and diagnosis of the disease [ 26 ]. In the United States, 85% of dietitian nutritionists were knowledgeable when assessed in five knowledge questions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, dietitians had a 73% score in the knowledge about appropriate food for CeD and 69% in the knowledge related to screening and diagnosis of the disease [ 26 ]. In the United States, 85% of dietitian nutritionists were knowledgeable when assessed in five knowledge questions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The actual surge in incidence, wheat content, gluten intake, CD-related T-cell stimulatory epitopes in wheat, usage in the processed food industries, nutritional deficiencies, changing phenotype and the fact that gluten is potentially detrimental to humankind health, make the RDNs role more complex, difficult but challenging. The most recent self-reported knowledge of the RDNs in GFD concluded that "RDNs may need more reinforcement on identification and treatment of nutritional deficiencies of CD" [5], but it seems that their role in the CD team is much vaster and GFD is a tough alley in a torrid time. As said, GFD for the RDNs dealing with CD is neither a solved problem nor a "closed case".…”
Section: Discussionmentioning
confidence: 99%
“…The cellulars' app is expanding and it becomes difficult to monitor, review, and compare them for their reliability and accuracy [8,9,10,11,12]. This problem is expanded due to the fact that the internet is the preferred resource for RDNs self and patients educations [5,13]. More than 20 on-line sources of information on CD and GFD are available [14].…”
Section: Gfd Is Not Standardized and Its CD Customers Are Quite Confusedmentioning
confidence: 99%
See 2 more Smart Citations